In vivo MRI analysis of depth‐dependent ultrastructure in human knee cartilage at 7 T. (25th June 2013) - Garnov, Nikita; Gründer, Wilfried; Thörmer, Gregor; Trampel, Robert; Turner, Robert; Kahn, Thomas; Busse, Harald
Abstract : Signal intensities of T 2 ‐weighted magnetic resonance images depend on the local fiber arrangement in hyaline cartilage. The aims of this study were to determine whether angle‐sensitive MRI at 7 T can be used to quantify the cartilage ultrastructure of the knee in vivo and to assess potential differences with age. Ten younger (21–30) and ten older (55–76 years old) healthy volunteers were imaged with a T 2 ‐weighted spin‐echo sequence in a 7 T whole‐body MRI. A "fascicle" model was assumed to describe the depth‐dependent fiber arrangement of cartilage. The R/T boundary positions between radial and transitional zones were assessed from intensity profiles in small regions of interest in the femur and tibia, and normalized to cartilage thickness using logistic curve fits. The quality of our highly resolved (0.3 × 0.3 × 1.0 mm 3 ) MR cartilage images were high enough for quantitative analysis (goodness of fit R 2 = 0.91 ± 0.09). Between younger and older subjects, normalized positions of the R/T boundary, with value 0 at the bone–cartilage interface and 1 at the cartilage surface, were significantly ( p < 0.05) different in femoral (0.51 ± 0.12 versus 0.41 ± 0.10), but not in tibial cartilage (0.65 ± 0.11 versus 0.57 ± 0.09, p = 0.119). Within both age groups, differences between femoral and tibial R/T boundaries were significant. Using a fascicle model and angle‐sensitive MRI, the depth‐dependent anisotropic fiber arrangement of knee cartilage could be assessed in vivo from a single 7 T MR image. The derived quantitative parameter, thickness of the radial zone, may serve as an indicator of the structural integrity of cartilage. This method may potentially be suitable to detect and monitor early osteoarthritis because the progressive disintegration of the anisotropic network is also indicative of arthritic changes in cartilage. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : Ten younger (21–30) and ten older (55–76 years old) healthy volunteers were imaged with a T 2 ‐weighted spin‐echo sequence in a 7 T whole‐body MRI. Applying a "fascicle" model of the collagen‐fiber arrangement, the boundary positions between radial and transitional zones were assessed from intensity profiles in small ROIs in the femur and tibia, and normalized to cartilage thickness. The radial zone in the femoral cartilage of younger volunteers has been found to be significantly thicker than that of older ones.